(untitled) (Global Journal of Medical Research, 2022)
Purpose: The COVID-19 pandemic has resulted in a heavy toll on public health. The adverse health outcomes have affected the public physically, mentally and emotionally. Waves during the pandemic have resulted in lockdowns that limited people’s ability to interact socially. Due to the novel nature of the disruptions the emotional effects of COVID related lock downs have not been adequately studied. This study assessed the effects of the Jan-Feb 2022 COVID wave related lockdown on young adults aged 18 to 25 in the 11 counties that form the Detroit Metro area in the State of Michigan in the United States of America. Methods: A survey instrument was developed using well validated Depression Anxiety Stress Scales-21 (DASS-21) along with other questions related to demographics, impact of COVID and methods used for obtaining advice. The survey was electronically shared with the target population in the Detroit Metro area with the help of Centiment, a market research company.